2006
DOI: 10.1007/s00198-006-0112-3
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates in pregnancy and lactation-associated osteoporosis

Abstract: PLO is therefore associated with significant morbidity, a high prevalence of recognized risk factors for osteoporosis and a risk of recurrence in subsequent pregnancies. Bisphosphonate therapy administered soon after presentation substantially increases spinal bone density in patients with PLO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
1
21

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(161 citation statements)
references
References 30 publications
3
121
1
21
Order By: Relevance
“…21 It is often associated with active osteoporotic changes and low BMD, 22,23 and therefore the phenomenon has been attributed to the presence of microfractures in the area.…”
Section: Clinical Features Of Bml Syndromesmentioning
confidence: 99%
“…21 It is often associated with active osteoporotic changes and low BMD, 22,23 and therefore the phenomenon has been attributed to the presence of microfractures in the area.…”
Section: Clinical Features Of Bml Syndromesmentioning
confidence: 99%
“…Bundan dolayı olayın osteopeni zemininde mi, yoksa osteoporoz zemininde mi olduğu net ayırt edilememektedir (12) ve GİO'nun, gebeliğin bir sonucu mu olduğu, yoksa gebelik öncesi düşük KMY ile mi ilişkili olduğu kesinleşmemiştir. Etiyolojisi belirsiz olsa da, birinci derece yakınında GİO varlığı, düşük VKİ, fiziksel inaktivite, kötü beslenme, yetersiz kalsiyum alımı ve sigara kullanımı gibi bazı risk faktörleri belirlenmiştir (6,13,14). Sekonder osteoporoz nedenlerinin varlığını da risk faktörleri arasında sayan yayınlar mevcuttur (10,12).…”
Section: Discussionunclassified
“…Nutritional calcium and activated vitamin D3 14) are given to replenish calcium. If accelerated bone resorption continues, bisphosphonate treatment is needed 15) . However, it has been reported that bisphosphonate could be teratogenic for the embryo.…”
Section: Discussionmentioning
confidence: 99%